Blessings the Tsoknyi Nangchen nuns of Tibet - Hitchcock, Victress; Gere, Richard 1949-; Tshogs-gnyis-rin-po-che 1966- (Pundarika Foundation, 2010)
"The purpose of this feature-length documentary is to expand awareness of the Nangchen Nuns, to explore the roots of their wisdom and compassion and to show how we, as ordinary human beings seeking happiness in a modern world, can find that same thread of sanity and inner strength in the everyday confusion of our lives"--Http://www.pundarika.org
DVD-R.. - Facilitator's guide laid in container. - This disc is a recorded DVD and may not play in all DVD players or drives
Narrator, Richard Gere; Tibetan narrator, Yangchen Drongpa
Associate producer, Amber Bemak ; editor, Victress Hitchcock ; translation, Tashi Gyaltsen, Tesola, Ani Jimpa
Keywords: Tsoknyi Rinpoche; Buddhist nuns / China / Tibet Autonomous Region; Film; DVD-Video